2005
DOI: 10.4049/jimmunol.175.2.1192
|View full text |Cite
|
Sign up to set email alerts
|

An Intact Phosphocholine Binding Site Is Necessary for Transgenic Rabbit C-Reactive Protein to Protect Mice against Challenge with Platelet-Activating Factor

Abstract: C-reactive protein (CRP), an acute phase protein in humans and rabbits, is part of the innate immune system. The role of CRP in host defense has been thought to be largely due to its ability to bind phosphocholine, activate complement, and interact with IgGRs (FcγRs). We have shown previously that transgenic rabbit CRP (rbCRP) protects mice from lethal challenges with platelet-activating factor (PAF). To investigate the mechanism of this protection, we created additional lines of transgenic mice that express e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Third, considering that the t 1/2 of injected CRP in mice is only 4 h (40, 41), it is evident that, after a day of infection when the effect of CRP was visible, CRP may not be present in the blood. Fourth, in the CRPmediated protection of mice challenged with platelet-activating factor, complement was not found to participate (42)(43)(44). Taken together, the activation of complement by bacteria, but not the activation of complement by CRP, could be responsible for the protection of mice from infection.…”
Section: Discussionmentioning
confidence: 89%
“…Third, considering that the t 1/2 of injected CRP in mice is only 4 h (40, 41), it is evident that, after a day of infection when the effect of CRP was visible, CRP may not be present in the blood. Fourth, in the CRPmediated protection of mice challenged with platelet-activating factor, complement was not found to participate (42)(43)(44). Taken together, the activation of complement by bacteria, but not the activation of complement by CRP, could be responsible for the protection of mice from infection.…”
Section: Discussionmentioning
confidence: 89%
“…The mechanisms responsible for these effects are not well understood, although a direct inhibitory effect of CRP on neutrophil chemotaxis was proposed (8,11,12). CRP has also been shown to interact with PAF, and inhibition of PAF was proposed to account for its protective effect on PAF-induced shock (13). We have shown that CRPmediated protection against endotoxin shock requires Fc␥R and is associated with the induction of IL-10 and suppression of IL-12 synthesis (14).…”
Section: -Reactive Protein (Crp)mentioning
confidence: 86%
“…CRP has been shown to block the attachment of PCh-expressing bacteria to the receptors for platelet-activating factor on the host cells (42). In addition, the PCh-binding ability of CRP was required for the protection of mice from challenge with plateletactivating factor (43).…”
Section: Discussionmentioning
confidence: 99%